The efficacy of scaling root planing to inflammation biomarker of periodontitis patients with atherosclerosis - Sekar SAFITRI; Agus SUSANTO; Ina HENDIANI (Journal of Syiah Kuala Dentistry Society, 2021)
ABSTRACT Periodontitis is a disease of surrounding dental tissue with a prevalence of 74.1% inIndonesia. Many studies show periodontitis plays a role in the progression of atherosclerosis. Therelationship between these two conditions shows that scaling root planing intervention can reduce therisk of atherosclerosis. This study aimed to know the efficacy of scaling root planing on changes ininflammatory biomarkers in periodontitis patients with atherosclerosis. This systematic literature reviewwas conducted using the Rapid Review method that refers to the Preferred Reporting Items forSystematic Review and Meta-Analysis (PRISMA) guidelines. Electronic searches were carried out from 4electronic databases, including the National Library of Medicine (Medline / PubMed), The CochraneLibrary, EbscoHOST, and SAGE Journal. Inclusion and exclusion criteria selected 6 RCT articles to beanalyzed qualitatively. Within 2 to 6 months, research in 6 RCT articles showed the results insignificantly reducing CRP levels as the main biomarkers of atherosclerosis after scaling root planingintervention. Other biomarkers that were also assessed are cytokines levels, lipid profile components,WBC, and fibrinogen. Overall results showed a positive effect of scaling root planing intervention inreducing the inflammatory biomarker levels of atherosclerosis in periodontitis patients withatherosclerosis. The treatment of scaling root planing is considered effective in reducing theinflammatory biomarker levels of atherosclerosis in periodontitis patients with atherosclerosis to reducethe level of risk. KEYWORDS: scaling root planing, inflammatory biomarker, atherosclerosis